Visual analytics of Hebrew manuscripts codicological metadata - Pateiro, T.; Marques de Matos, D.; Cardoso, E. (1st KDD Workshop on Data Science for Digital Art History: tackling big data Challenges, Algorithms, and Systems, 2018)
This paper presents the CodicoDaViz research project, developed with the goal of applying data visualisation techniques to the field of codicology. Adding to the multidisciplinary nature of digital humanities (DH), this project brings together a group of experts of DH, business intelligence and computer science. Using Hebrew manuscript data as a starting point, CodicoDaViz proposes an environment for exploratory analysis to be used by Humanities experts to deepen their understanding of codicological data, and to formulate new research hypotheses. In this paper we demonstrate how data visualisation was instrumental in understanding and structuring the dataset. Examples of the dashboards that have been designed (in Tableau) to enable an interactive and ad-hoc exploration of data are also discussed.